Վիզուալիզացիոն մեթոդների կիրառումը ժամանակակից ճառագայթային ուռուցքաբանությունում - Անտոնյան, Պ. Մ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В связи с широким внедрением в клиническую практику современных методов лучевой терапии, позволяющих увеличить точность доставки поглощенных доз, оптимизация планирования облучения становится особенно актуальной. В обзоре рассмотрена роль современных методов визуализации на всех этапах проведения лучевой терапии онкологических заболеваний – симуляции, планирования, мониторинга облучения и оценке эффективности лечения. Показана перспективность применения морфологических и функциональных методик МРТ, ПЭТ/КТ с метаболическими и рецепторными маркерами, УЗИ, позволяющих повысить точность планирования и обеспечить эффективный мониторинг лечебного процесса. In connection with the widespread introduction of new methods of the radiation therapy into the clinical practice, which makes it possible to increase the accuracy of delivery of the absorbed doses, the optimization of radiotherapy planning becomes especially relevant. The review describes the role of modern methods of visualization in all stages of radiation therapy for oncological diseases – simulation, planning, dose delivery monitoring and evaluation of treatment effectiveness. The prospects of using morphological and functional methods of MRI, PET/CT with metabolic and receptor markers and ultrasonography, which can upgrade precision of the radiation therapy planning and improve the monitoring of therapeutic processes, are shown.
Keywords: Ուռուցքաբանություն (ներառյալ քաղցկեղ)